A new deep-reef scorpionfish (Teleostei, Scorpaenidae, Scorpaenodes) from the southern Caribbean with comments on depth distributions and relationships of western Atlantic members of the genus - Baldwin, Carole C. (Zookeys, 2016)
Abstract. A new species of scorpionfish, Scorpaenodes barrybrowni Pitassy & Baldwin, sp. n. which is described, was collected during submersible diving in the southern Caribbean as part of the (DROP). It differs from the other two western Atlantic species of the genus, Scorpaenodes caribbaeus and Scorpaenodes tredecimspinosus, in various features, including its color pattern, having an incomplete lateral line comprising 8–10 pored scales, tending to be more elongate, usually having the 11(th)–12(th) pectoral-fin rays elongate, and by 20–23% divergence in the (COI) DNA barcode sequences. It further differs from one or the other of those species in head spination and in numbers of soft dorsal-fin rays, pectoral-fin rays, and precaudal + caudal vertebrae. Inhabiting depths of 95–160 m, the new species is the deepest western Atlantic member of the genus (Scorpaenodes caribbaeus occurs at depths < 35 m and Scorpaenodes tredecimspinosus from 7 to 82 m). DNA barcode data do not rigorously resolve relationships among the ten species of the genus for which those data are available.